Transcriptomic Regulation of Muscle Mitochondria and Calcium Signaling by Insulin/IGF-1 Receptors Depends on FoxO Transcription Factors - Bhardwaj, Gourav; Penniman, Christie M.; Klaus, Katherine; Weatherford, Eric T.; Pan, Hui; Dreyfuss, Jonathan M.; Nair, K. Sreekumaran; Kahn, C. Ronald; O’Neill, Brian T. (Frontiers in Physiology, 2022)
Insulin and IGF-1, acting through the insulin receptor (IR) and IGF-1 receptor (IGF1R), maintain muscle mass and mitochondrial function, at least part of which occurs via their action to regulate gene expression. Here, we show that while muscle-specific deletion of IR or IGF1R individually results in only modest changes in the muscle transcriptome, combined deletion of IR/IGF1R (MIGIRKO) altered >3000 genes, including genes involved in mitochondrial dysfunction, fibrosis, cardiac hypertrophy, and pathways related to estrogen receptor, protein kinase A (PKA), and calcium signaling. Functionally, this was associated with decreased mitochondrial respiration and increased ROS production in MIGIRKO muscle. To determine the role of FoxOs in these changes, we performed RNA-Seq on mice with muscle-specific deletion of FoxO1/3/4 (M-FoxO TKO) or combined deletion of IR, IGF1R, and FoxO1/3/4 in a muscle quintuple knockout (M-QKO). This revealed that among IR/IGF1R regulated genes, 97% were FoxO-dependent, and their expression was normalized in M-FoxO TKO and M-QKO muscle. FoxO dependent genes were related to oxidative phosphorylation, inflammatory signaling, and TCA cycle. Metabolomic analysis showed accumulation of TCA cycle metabolites in MIGIRKO, which was reversed in M-QKO muscle. Likewise, calcium signaling genes involved in PKA signaling and sarcoplasmic reticulum calcium homeostasis were markedly altered in MIGIRKO muscle but normalized in M-QKO. Thus, combined loss of insulin and IGF-1 action in muscle transcriptionally alters mitochondrial function and multiple regulatory and signaling pathways, and these changes are mediated by FoxO transcription factors.